5 STAR HOTELS SERVICE QUALITY IN MONGOLIA - Lkhamtseden.B*,; Degidbadam.D, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Service quality is considered substantial when it comes to define organizational success. The winning strategy is to deliver excellent quality service to customers. By providing quality service, organizations can sustain customers’ confidence and competitive advantages over their competitors. This study scrutinizes the effects of various elements of hotel industry which affects customer satisfaction. The purpose of this exploratory study was to investigate and assess guest perceptions of service quality in 5 star hotels in Mongolia. A convenient sample of 285 guests drawn from four 5 star hotels was used in the analytical stage. Overall the clearly indicate significant differences between hotel guests’ expectations and their actual experiences, thus highlighting managerial implications. The findings indicated, as a whole that the hotel customers’ perceptions of service quality provided by the hotel industry were lower than their expectations and the gaps between customers’ expectations and perceptions were significant.